Coverage of women’s agricultural activities in Nigerian daily newspapers (1997)
This study investigated the coverage and direction of women's agricultural activities in Nigerian daily newspapers between 1970 and 1990. ln order to attain the research objectives, 6408 editions or 10 daily newspapers were randomly selected for the 21-year period. These newspaper editions were content analysed for types of women activities reported and prominence and direction of the reported activities. The results indicate that there has been a steady increase in the number of women's agricultural activities reported in Nigerian dailies. While the amount of space allocated to women's activities is small, the reports are favourab!e but not prominently located.